Analisis Corporate Social Responsibility dan Kualitas Pelayanan terhadap Loyalitas Nasabah di Bank Syariah Indonesia - Uswatun Mar’atu Soleha; Selly Puspita Sari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This study aims to test and analyze the effect of corporate social responsibility and service quality on customer loyalty. This research sample was obtained from Bank Syariah Indonesia savings customers. Based on the data obtained, there are 18.4 million BSI savings customers. This research uses Quantitative methods and the sampling technique used in this study is the Purpossive Sampling technique, which is a sampling technique of data sources with certain considerations. Data collection was carried out using primary and secondary data techniques, primary data in the form of questionnaires distributed to 100 respondents and secondary data in the form of BSI CSR Financial Statements, books, journals, and theses. The data analysis technique used is multiple linear regression analysis using SPSS program version 26.0. The results of the t-test calculation on the variable X1 Corporate Social Responsibility (CSR) with a calculated t value of 3.372 > t table 1.984, meaning that Corporate Social Responsibility affects Customer Loyalty. Variable X2 Service Quality with a calculated t value of 4,432 > t table 1,984, meaning that Service Quality affects Customer Loyalty.